2017
DOI: 10.1002/brb3.734
|View full text |Cite
|
Sign up to set email alerts
|

Propofol‐induced downregulation of NR2B membrane translocation in hippocampus and spatial memory deficits of neonatal mice

Abstract: BackgroundThousands of infants and children are undergoing anesthesia around the world every day. But impacts of anesthetics on the developing neural system remain unclear yet. Previous evidence showed that anesthesia might affect the developing neural system. Thus, early‐life anesthesia becomes a critical issue in clinical pediatric practice. Hence, propofol, a short‐acting and widely applied intravenous anesthetic, has been gaining focus upon neonatal anesthesia.MethodsFifty‐four male C57BL/6J mice were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…From a molecular perspective, NMDAR are tetrameric structures assembled from two obligatory GluN1 subunits and two GluN2A (formerly NR2A) or GluN2B (formerly NR2B) subunits. Evidence suggests that the NR2B subunit in the hippocampus is particularly important for NMDAR channel function ( Akashi et al, 2009 ), long-term potentiation (LTP), and associated cognitive functions such as spatial learning ( Clayton et al, 2002 ; Wang et al, 2017 ; Xu et al, 2017 ). Accordingly, numerous studies have suggested that NR2B, rather than NR2A, is involved in schizophrenia in humans ( Loftis and Janowsky, 2003 ; Geddes et al, 2014 ) and schizophrenia-like behaviors induced by NMDAR antagonists in rodents ( Jiménez-Sánchez et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…From a molecular perspective, NMDAR are tetrameric structures assembled from two obligatory GluN1 subunits and two GluN2A (formerly NR2A) or GluN2B (formerly NR2B) subunits. Evidence suggests that the NR2B subunit in the hippocampus is particularly important for NMDAR channel function ( Akashi et al, 2009 ), long-term potentiation (LTP), and associated cognitive functions such as spatial learning ( Clayton et al, 2002 ; Wang et al, 2017 ; Xu et al, 2017 ). Accordingly, numerous studies have suggested that NR2B, rather than NR2A, is involved in schizophrenia in humans ( Loftis and Janowsky, 2003 ; Geddes et al, 2014 ) and schizophrenia-like behaviors induced by NMDAR antagonists in rodents ( Jiménez-Sánchez et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, iso urane up-regulated extrasynaptic NR2B in the hippocampus in elderly rats and impaired cognitive function [24]; and iso urane or sevo urane upregulated NR2B in the hippocampus, facilitated LTP in CA1 area, and improved cognition in adult mice [14,16]. Sevo urane induced NR1 and NR2B up-regulation, NR2A down-regulation in the PFC, and caused cognitive de cits in adolescent rats [71], while propofol down-regulated NR1, NR2B, NR2A, and PSD-95 in the PFC of developing rat brain, and caused long-term cognitive dysfunction [17,72]. The possible reasons for this discrepancy might be different ages, species of animals, and strategies of drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The NR1 subunit is an essential part of NMDAR, while the NR2 subunits, especially NR2A and NR2B, are mainly distributed in the adult rat hippocampus, and primarily regulate the function of the receptor [13]. Previous studies suggested that inhalation and intravenous anesthetics exhibited a differential effect on the expression of the NR2B subunit, which was accompanied by changes in cognitive function [14][15][16][17]. For example, iso urane or sevo urane exposure alone could improve cognitive function via an upregulation of NR2B subunit in the hippocampus [14,16], while propofol exposure decreased the level of NR2B subunit in the hippocampus and induced spatial memory de cits, suggesting that upregulation of NR2B exerts the neuroprotective effect [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Wang et al. ). A volume of 10 mL/kg is considered the highest recommended amount for i.p., and this dose was chosen to elicit a maximal response.…”
Section: Introductionmentioning
confidence: 98%